THE EFFECT OF RELIGIOSITY, FINES, AND SHARIA FINANCIAL LITERACY ON CUSTOMER COMPLIANCE IN FULFILLING OBLIGATIONS BY COLLECTION ACTIVITIESAS AN INTERVENING VARIABLEIN THE UUS OF PT BANK SUMUT, SIBOLGA CITY - Rama Indra Jaya; Muhammad Ramadhan; Nurbaiti Nurbaiti (Pena Cendekia Insani, 2025)
This study examines the influence of religiosity, penalties, and Islamic financial literacy on customer compliance in fulfilling financing obligations, with collection activities as an intervening variable at the Sharia Business Unit (UUS) of Bank Sumut in Sibolga City. The study is motivated by the persistent issue of delayed payments and non-compliance, despite relatively high levels of religiosity and the increasing trend of Islamic financial literacy among customers. A quantitative approach was employed, with primary data collected through questionnaires distributed to 93 respondents selected using accidental sampling. Data were analyzed using multiple linear regression and path analysis (SmartPLS 4.0) to identify direct and indirect effects among variables. The results reveal that religiosity, penalties, and Islamic financial literacy significantly and positively affect collection activities, and jointly influence customer compliance. Partially, religiosity and Islamic financial literacy have a significant positive effect on compliance, whereas penalties demonstrate a positive yet reactive effect, functioning mainly as a deterrent mechanism. Furthermore, collection activities mediate the relationship between the independent variables and compliance, indicating that effective collection procedures strengthen the influence of religious values, penalty perceptions, and financial knowledge on customer behavior. These findings suggest that customer compliance in Islamic banking is not solely shaped by religious conviction and knowledge, but also by operational interventions conducted in a professional, educative, and persuasive manner. The study offers both theoretical contributions to Islamic financial behavior literature and practical implications, emphasizing the need to enhance Islamic financial literacy programs, refine socially oriented penalty mechanisms, and optimize collection strategies to promote disciplined and value-based compliance.